EFFECT OF CU ADDITION ON STACKING FAULT ENERGY, MICROSTRUCTURE, AND MECHANICAL PROPERTIES OF COCRWNI ALLOY FOR BIOMEDICAL APPLICATION - Tamimi Prasetya Aji, Syamsul
The effect of Cu on the stacking fault, microstructure, and mechanical properties of Haynes 25 CoCrWNi alloy has been studied to develop an alloy for cardiac stent biomedical applications. Cobalt alloys have disadvantage of poor formability. The addition of Cu to the CoCrWNi alloy can increase the value of stacking fault energy, biocompatibility, and formability. This research studies the microstructure, mechanical properties, and stacking fault energy of the CoCrWNi alloy with the addition of Cu. CoCrWNi alloy was added with Cu using argon arc melting in an argon atmosphere with a concentration of 1.5- 4.5% weight percentage and homogenized in a horizontal tube furnace at 1000 oC for 8 hours. The XRD test showed that the addition of Cu up to 4.5% weight percentage stabilized the fcc-? phase and suppressed the formation of the hcp-? phase in the CoCrWNi alloy. Microstructural observations of the CoCrWNi alloy indicated that there was twinning in the alloy without the addition of Cu. CoCrWNi alloy with the addition of Cu produces a dendritic-shaped microstructure. The hardness and compressive test mechanical properties of the CoCrWNi alloy decreased after the addition of Cu. The addition of Cu can prevent the formation of stacking faults in the microstructure. CoCrWNi alloy without the addition of Cu which has uniaxial hardness and stress values of 455.3 HV and 728.08 MPa. Whereas the CoCrWNi alloy with the addition of 4.5 wt.% Cu alloy produced the lowest values of hardness and uniaxial compressive stress, 270.2 HV and 141.97 MPa. The CoCrWNi-Cu alloy samples that experienced deformation after the compression test experienced an increase in hardness values. This is the effect of strain induced martensitic transformation (SIMT) in encouraging the formation of martensite and reduction of grain size. The CoCrWNi-Cu alloy can be calculated for the value of the stacking fault energy using the XRD, first-principle, and thermodynamic analysis methods. The addition of Cu alloying elements can increase the value of the stacking fault energy of the CoCrWNi alloy. The stacking fault energy values affect the mechanical properties of the CoCrWNi-xCu alloy. A higher stacking fault energy value indicates a lower stacking fault probability, so it tends to be more difficult to form a stacking fault.